THE METHODS AND STRATEGIES OF TEACHING VOCABULARY (Academicia Globe: Inderscience Research, 2022)
This article focuses on one of the aspects that can build the four skills in  English and that is known as vocabulary. There are some reasons that make vocabulary is important to be learned. First, it will be hard for the learners if they must study English with limited words in their mind. In this article is described the main features and methods of teaching and learning vocabulary and their effectiveness for young learners